Eventration of diaphragm with gastric volvulus: A case report - John J. S. Martis; Abijith Shetty; Roy Alban Frank; Vijayakumar Vijin (Wolters Kluwer Medknow Publications, 2015)
Gastric volvulus is a rare but potentially life threatening cause for upper gastrointestinal obstruction. It is an abnormal rotation of one part of the stomach around another which can manifest with acute, intermittent or chronic symptoms. Historically first reported case of gastric volvulus was in 1866 by Berti and the first operation for this condition was performed in 1897 by Berg. Since then there are approximately 400 cases reported in the literature. We report a case of acute gastric volvulus associated with eventration of left hemidiaphragm in a 60 years old female who presented with features of gastric outlet obstruction.